2020
DOI: 10.33220/1026-3365.135.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Age structure of European ash (Fraxinus excelsior L.) forests in the Left- Bank Forest-Steppe of Ukraine

Abstract: The age structure of European ash stands in the forest fund of ten forest enterprises from Sumy, Kharkiv and Poltava regions was analyzed considering forest site conditions, stand origin, site index and ash proportion in the forest composition. The average age of ash stands is 68 years for the Left-Bank Forest-Steppe. On average from 46.1 % to 81.6% of European ash stands survive up to the V age class. The average age of ash stands is the highest in the forest-steppe part of Sumy Region in D2 and D3, in Kharki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
8
0
3
Order By: Relevance
“…Thus, at different times, studies of the productivity of pine stands on the left bank of the Forest-Steppe were conducted by O.V. Tovstukha (2012) The purpose of this study was statistical confirmation or refutation of the null hypothesis about the significance of the difference between the average stand parameters in modal pine stands of the Forest-Steppe zone of Ukraine in terms of groups of stands differing in growth region, origin, and composition, as well as determining the groups according to which further forest inventory standards for modal Scots pine stands should be compiled and their detailed inventory characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, at different times, studies of the productivity of pine stands on the left bank of the Forest-Steppe were conducted by O.V. Tovstukha (2012) The purpose of this study was statistical confirmation or refutation of the null hypothesis about the significance of the difference between the average stand parameters in modal pine stands of the Forest-Steppe zone of Ukraine in terms of groups of stands differing in growth region, origin, and composition, as well as determining the groups according to which further forest inventory standards for modal Scots pine stands should be compiled and their detailed inventory characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the age composition of elms in the region may also be important for the evaluation of the maturity age of this species. Studies of other forest tree species, in particular, Silver birch (Betula pendula Roth) (Meshkova, & Koshelyaeva , 2019) and European ash (Fraxinus excelsior L.) (Meshkova, & Borysova 2019) showed that the maturity age evaluated by growth dynamics is much higher than the actual age of tree mortality from disease in the face of the threat of epiphytoty, leading to a loss in the timber quality.…”
mentioning
confidence: 99%
“…According to this, the proportion of the stand area of each 10-year age class was estimated for each elm species and stand origin. Then the proportion of the stands' area, which survives up to a certain age, was estimated (Meshkova, & Borysova, 2019;Meshkova, & Koshelyaeva, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…та інші ентомошкідники (Krasnov et al, 2011). Наразі науковці приділяють значну увагу проблемам верхівкового всихання P. sylvestris, про що свідчать публікації у фахових виданнях (Vyshnevskyi & Turko, 2018;Meshkova et al, 2020;Ustskyi et al, 2020). Щодо досліджень кореневої губки, то в останні роки вони зменшились, відійшли на другий план, відповідно стало значно менше наукових публікацій за даною проблематикою у контексті формування та вирощування стійких лісових екосистем до збудника кореневої губки сосни звичайної.…”
unclassified